Real Commitment or Symbolic Legitimacy? Mattessich's Critique of the Deposit-on-Call Scheme - Yayuk Ari Priyani; Sri Iswati (Jurnal Akuntansi Publik Nusantara, 2026)
This study is based on Mattessich’s philosophy of accounting, using legitimacy theory as the analytical framework to examine the policy of placing state funds in the Deposit-on-Call scheme. The study aims to critically assess whether the policy reflects a real commitment or merely symbolic legitimacy. A qualitative approach with Critical Discourse Analysis (CDA) is employed. The data consist of official news reports and policy documents related to the Minister of Finance’s policy and its public discourse. The analysis is conducted through three stages: linguistic analysis of policy texts, discursive practice analysis to identify rhetorical strategies and legitimacy narratives, and social practice analysis to evaluate the extent to which the policy represents substantive commitment or symbolic legitimacy. The findings indicate that the Deposit-on-Call policy demonstrates a dual character. On one hand, it reflects real commitment through objectives such as reducing bank funding costs, expanding credit capacity, and supporting productive sectors, particularly MSMEs. On the other hand, the policy also carries the risk of symbolic legitimacy if transparency and accountability in fund distribution are not effectively ensured. The legitimacy of the policy is therefore contingent upon the actual realization of credit distribution and the equitable impact on the real sector. If the funds only enhance banking liquidity without generating tangible benefits for the real economy, the policy risks becoming symbolic in nature, consistent with Mattessich’s critique of appearance without substantive societal impact.